2010
DOI: 10.1007/s11626-010-9325-z
|View full text |Cite
|
Sign up to set email alerts
|

Culture of newborn monkey liver epithelial progenitor cells in chemical defined serum-free medium

Abstract: Studies with hepatic progenitor cells from non-human primates would allow better understanding of their human counterparts. In this study, rhesus monkey liver epithelial progenitor cells (mLEPCs) were derived from a small piece of newborn livers in chemical defined serum-free medium. Digested hepatic cells were treated in Ca(2+)-containing medium to form cell aggregates. Two types of cell aggregates were generated: elongated spindle cells and polygonal epithelial cells. Elongated spindle cells were expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Having considered all these facts, we hypothesized that TGF-β would induce hepatic epithelial progenitors to convert into myofibroblasts-like cells through the process of EMT. Previously, we reported the isolation of liver epithelial progenitor cells from both adult and newborn monkeys (Jin et al 2009;Ji et al 2010). Here, we provide in vitro evidence for the first time that adult rhesus monkey liver epithelial progenitor cells, mLEPCs, acquire myofibroblastslike phenotype via EMT.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Having considered all these facts, we hypothesized that TGF-β would induce hepatic epithelial progenitors to convert into myofibroblasts-like cells through the process of EMT. Previously, we reported the isolation of liver epithelial progenitor cells from both adult and newborn monkeys (Jin et al 2009;Ji et al 2010). Here, we provide in vitro evidence for the first time that adult rhesus monkey liver epithelial progenitor cells, mLEPCs, acquire myofibroblastslike phenotype via EMT.…”
Section: Introductionmentioning
confidence: 61%
“…Adult mLEPCs were isolated and characterized as previously described (Jin et al 2009;Ji et al 2010). FACS analysis of cell surface molecules revealed that adult mLEPCs were homogenously positive for hepatic progenitor markers such as E-cad (Nitou et al 2002;Nierhoff et al 2005), CD44 (Kon et al 2006) and CD73 (Kakinuma et al 2009; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further research is needed to evaluate the HSC potential of hepatic progenitors. Previously, we reported the isolation of rhesus monkey liver epithelial progenitor cells (mLEPCs) from both adult and newborn liver (2, 3). Here, we have reported that fluorescence‐activated cell sorting (FACS)‐purified E‐cadherin‐positive adult mLEPCs expressed HSCs‐specific protein when co‐cultured with monkey ear skin fibroblasts (MESFs).…”
mentioning
confidence: 99%
“…Adult mLEPCs were isolated and prepared as described previously (2, 3). Briefly, cell aggregates were prepared in Ca 2+ ‐containing medium from fresh digested hepatic cells.…”
mentioning
confidence: 99%